Text Segment Length Can Impact Emotional Reactions to Narrative Storytelling. Issue 3 (3rd April 2019) - Pham, Hellen; Sanchez, Christopher A.
ABSTRACT: Previous studies have suggested that simple physical changes in how a text is presented can have profound effects on how a text is learned and processed. Although research on text learning does suggest that physical changes in presentation can impact remembering, it may be possible that presentation differences (e.g., presenting text in multiple shorter segments) also produce a quantitatively different emotional reaction in a reader. The potential impact of presentation differences on the emotional reaction of the reader is the focus of the current set of studies. In two experiments that used different narrative texts, participants read in differently segmented narrative presentations. Participants were evaluated for both their memory of the text and their emotional reaction to the text. Results were identical across both experiments, such that despite equivalent memory, shorter text presentations produced higher estimates of emotional reaction and reading enjoyment. These results suggest that physical presentation characteristics can impact how a reader emotionally engages with a narrative text, and these characteristics might present an interesting opportunity to enhance (or detract) from the intrinsic emotional value of a given text.